Comparação de sistemas de avaliação de dietas para bovinos no modelo de produção intensiva de carne. Confinamento de tourinhos jovens - Sampalo, Alexandre Amstalden Moraes [UNESP]; De Brito, Rodolfo Marques [UNESP]; De Moraes Carvalho, Ricardo [UNESP] (FapUNIFESP (SciELO), 2002)
Thirty 3/4 Canchim + 1/4 Nelore young bulls with 417 kg of body weight and 15 months of age, were confined during 84 days. The animals were fed with diets composed with corn silage, corn grain, cottonseed meal, soybean meal, whole soybean and mineral mix, adjusted in agreement with the recommendations of the Metabolizable Protein System (MP), Cornell Net Carbohydrate and Protein System (CNCPS) and Intestine Digestible Protein System (PDI), for predicted body weight gain of 1.3 kg/head/day. The daily body weight gain did not differ among treatments CNCPS, MP and PDI, with 1.51; 1.48; and 1.13 kg/head, respectively. The economic analysis revealed net profit of R$116.25; R$148.30; and R$108.51/head for CNCPS, MP and PDI systems, respectively. The diets adjusted by CNCPS and MP systems provided superior animal performance than that expected, while the diet adjusted by PDI system did not allow the predicted body weight gain.
Comparison of diet evaluation systems for cattle in an intensive beef production model. Feedlot of young bulls
Keywords: Beef cattle; Corn silage; Cottonseed meal; Requirements; Soybean meal; carbohydrate; cotton seed oil; mineral; age; animal food; beef cattle; body weight; corn; digestion; economic aspect; food composition; grain; intestine; meat industry; nonhuman; prediction; silage; soybean; weight gain; Animalia; Bos taurus; Glycine max; Gossypium hirsutum; Micropus; Zea mays